TO DETERMINE THE ASSOCIATION OF MATERNAL ANEMIA WITH PERINATAL OUTCOME IN TERTIARY CARE HOSPITAL - Baig, Jehan Ara Rafiq; Jamal, Muhammad Musarrat; Jamal, Javeria; Musarrat, Maniha (Pakistan Armed Forces Medical Journal, 2020)
Objective: Determine the association of maternal anemia with perinatal outcome in tertiary care hospital. Study Design: Prospective study. Place and Duration of Study: Department of Gynecology and Obstetrics, Combined Military Hospital, Sialkot from Jan 2018 to Dec 2018. Methodology: A total of 844 pregnant women were enrolled during study period. Maternal anemia, was categorized keeping with WHO criteria based on hemoglobin levels: no anemia/normal (≥11 g/dl), mild (10–10.9 g/dl), moderate (≥7-9.9 g/dl) or severe (<7 g/dl). Perinatal outcome included were preterm delivery, low birth weight, intrauterine growth retardation, intrauterine deaths, low Apgar and perinatal complications leading to neonatal intensive care unit admissions. Results: Out of 844 pregnant women studied, 558 (66.11%) were anemic (hemoglobin <11 g/dl), and 286 (33.89%) women had hemoglobin ≥11 g/dl and were labeled as non anemic. The risk of preterm delivery and low birth weight was 2.5 and 3 times higher among moderate to severely anemic women, newborns of these anemic mothers had 2.8 times increased risk of having an Apgar score of <5 at 1min and there was increased risk of intrauterine growth retardation for moderate to severely anemic mothers. Conclusion: Maternal anemia is associated with increased risk of preterm delivery, low birth weight babies, low APGAR, intrauterine growth retardation and increased perinatal mortality.